Antixenosis of bean genotypes to Chrysodeixis includens (Lepidoptera: Noctuidae) - Morando, Rafaela [UNESP]; Lopes Baldin, Edson Luiz [UNESP]; Cruz, Patricia Leite [UNESP]; Lourencao, Andre Luiz; Chiorato, Alisson Fernando (Empresa Brasil Pesq Agropec, 2015)
The objective of this work was to evaluate bean genotypes for resistance to soybean looper (Chrysodeixis includens). Initially, free-choice tests were carried out with 59 genotypes, divided into three groups according to leaf color intensity (dark green, light green, and medium green), in order to evaluate oviposition preference. Subsequently, 12 genotypes with high potential for resistance were selected, as well as two susceptible commercial standards. With these genotypes, new tests were performed for oviposition in a greenhouse, besides tests for attractiveness and consumption under laboratory conditions (26 +/- 2 degrees C, 65 +/- 10% RH, and 14 h light: 10 h dark photophase). In the no-choice test with adults, in the greenhouse, the 'IAC Jabola', Arcelina 1, 'IAC Boreal', 'Flor de Mayo', and 'IAC Formoso'genotypes were the least oviposited, showing antixenosis-type resistance for oviposition. In the free-choice test with larvae, Arcelina 4, 'BRS Horizonte', 'Perola', H96A102-1-1-1-52, 'IAC Boreal', 'IAC Harmonia', and 'IAC Formoso'were the less consumed genotypes, which indicates antixenosis to feeding. In the no-choice test, all genotypes (except for 'IAPAR 57') expressed moderate levels of antixenosis to feeding against C. includens larvae.

O objetivo deste trabalho foi avaliar genótipos de feijoeiro quanto à resistência a lagarta-falsa-medideira (Chrysodeixis includens). Inicialmente, foram realizados testes com chance de escolha com 59 genótipos, divididos em três grupos, de acordo com a intensidade de coloração das folhas (verde-escura, verde-clara e verde-médio), para avaliar a preferência quanto à oviposição. Em seguida, selecionaram-se 12 genótipos com grande potencial de resistência, assim como dois padrões comerciais suscetíveis. Com estes genótipos, realizaram-se novos ensaios de oviposição, em casa de vegetação, além de testes de atratividade e consumo, em condições de laboratório (26±2ºC, 65±10% UR e fotófase de 14 h luz: 10 h escuro). No teste sem chance de escolha, com adultos, em casa de vegetação, os genótipos 'IAC Jabola', Arcelina 1, 'IAC Boreal', 'Flor de Mayo' e 'IAC Formoso' foram os menos ovipositados, tendo apresentado resistência do tipo antixenose à oviposição. No teste com chance de escolha, com larvas, Arcelina 4, 'BRS Horizonte', 'Pérola', H96A102-1-1-1-52, 'IAC Boreal', 'IAC Harmonia' e 'IAC Formoso' foram os genótipos menos consumidos, o que indica antixenose à alimentação. No teste sem chance de escolha, todos os genótipos (exceto 'IAPAR 57') expressaram níveis moderados de antixenose à alimentação de larvas de C. includens.
Keywords: Common bean; Host plant resistance; Nonpreference; Resistance mechanisms; Soybean looper; Feijão-comum; Resistência de plantas hospedeiras; Não preferência; Mecanismos de resistência; Lagarta-falsa-medideira